Parity-Time Symmetric Nonlocal Metasurfaces: All-Angle Negative Refraction and Volumetric Imaging - Monticone, Francesco; Valagiannopoulos, Constantinos A.; Alù, Andrea (Physical review. X, 2016)
Lens design for focusing and imaging has been optimized through centuries of developments; however, conventional lenses, even in their most ideal realizations, still suffer from fundamental limitations, such as limits in resolution and the presence of optical aberrations, which are inherent to the laws of refraction. In addition, volume-to-volume imaging of three-dimensional regions of space is not possible with systems based on conventional refractive optics, which are inherently limited to plane-to-plane imaging. Although some of these limitations have been at least theoretically relaxed with the advent of metamaterials, several challenges still stand in the way of ideal imaging of three-dimensional regions of space. Here, we show that the concept of parity-time symmetry, combined with tailored nonlocal responses, enables overcoming some of these challenges, and we propose the design of a loss-immune, linear, transversely invariant, planarized metamaterial lens, with reduced aberrations and the potential to realize volume-to-volume imaging.